OVERCROWDING PATIENT AND IMPROVING EMERGENCY PATIENT FLOW IN EMERGENCY DEPARTMENT: A LITERATURE REVIEW - Dewi Kartikawati Ningsih (Journal of Nursing Science Update (JNSU), 2015)
Overcrowding discussion in emergency department (ED) has become a great issue over decade. The EDs plays a significant role as a frontline in hospital which performing good or bad quality of care. Identifying bottleneck relative to patient flow in the ED is one of important factor to determine the quality of care. The EDs can be considered as the heart of the hospital where increasing number of patient in the ED link to the increasing number of patients in the hospital. Therefore performing delivery of care in the ED particularly when its deal with overcrowding could represent the quality of care in hospital as a whole.The study aimed to explore factors related to overcrowding patient and improving emergency patient flow in emergency department. The study was about a literature review and the articlesused in the literature review were full text. The literature review methods were collected and analyzed articles about overcrowding emergency department, emergency department patient flow, the quality of service in emergency room and emergency department performance towards waiting time and length of visit. Articles collected through electronic database, science direct with keywords overcrowding the ED, the ED patient flow, emergency quality services. There were three factors that affect overcrowding patient: prolonged waiting time, triaging, and shortage of doctors and nurses ratio in the ED room. When those three factors are combined, the overcrowding patient in the ED could be handled and it may probably result to improving patient flow. The prolonged waiting time have created delayed of care, patient leaving without being seen/treatment and dissatisfaction among patients The same idea was presented that triaging somehow invent prolonged time especially for those patients in semi-urgent or non-urgent that need treatment between 61 minutes to 2 hours. Those patients are dominantly in the ED and if the patients do not understand triage system they become short-tempered and complaining. The last one was the number of emergency physician and nurses are being backbone of services, however, if it is still lack of number thus leading to troublesome which may significantly affect to effectiveness of care and patient safety. The findings from the above-cited studies suggested that assign fast track for semi-urgent and non-urgent patient should be treated and discharged promptly and properly. Also, expanding the number of physician and nurse staffs with the ratio 1 and 2 respectively as well as developing standardized job descriptions is mandatory. Moreover, extent inpatient bed capacity specifically to critical care unit and increase number of available room for emergency room admission. Keyword: overcrowding ED, ED patient flow, emergency quality services.